Forage production under silvipastural system - VAIRAVAN, K; GANECHE, C; KANNAN, S (The Indian Journal of Agricultural Sciences, 2014)
A study was carried out during 1993-98 with a tree species (Acacia senegal, Leucacna leucocephala, Gliricidia maculata and Casuarina equisetifolia) intercropped with 3 forage crops (Sorghum halepense, Cenchrus ciliaris and Stylosantlzes hamata) to find out the suitable combination of tree and forage crop for higher forage production on marginal lands. On the basis of 6 years, it WM observed that A. sellegal intercroppcd with S. hamata was the best combination for higher forage production followed by L. leucocephaia + S. hamata.